Teachers’ Job Satisfaction and Effective Implementation of the National Policy on Education in Public Junior Secondary Schools in Rivers State - Nancy Noble Nwanwa (International Journal on Integrated Education, 2026)
The study investigated the extent to which the extent to which teachers’ job satisfaction predict effective implementation of the National Policy on Education in public junior secondary schools in Rivers State, Nigeria. The study was based on two objectives, two research questions and two hypotheses tested at 0.05 level of significance. Herzberg's Two-Factor Theory served as the foundation for the study. The design used was a correlational design. The population comprised 1,122 administrative heads in the 374 Public Junior Secondary Schools in Rivers State. A sample of 561 administrative heads representing 50% of the population. Two instruments developed by the researcher titled “Teachers’ Job Satisfaction Questionnaire and Effective Implementation of the National Policy on Education Questionnaire” were used to collect data. The instruments consisted of 50 items designed based upon modified four-point Likert-type rating scale. Research questions were answered using simple regression analyses, and t-tests associated with simple regression were applied to test hypotheses 1-6 at 0.05 level of significance. The results showed that, to a moderate extent, teachers' adequate remuneration predict effective implementation of the National Policy on Education. To a low extent, teachers' recognition, predict effective implementation of the National Policy on Education. In conclusion, teachers' adequate remuneration is the most significant predictors, showing to a moderate extent of prediction. Conversely, teachers' recognition, was found to have a low extent of prediction. Among others, the researcher recommended that Rivers State Government and Universal Basic Education Board should ensure that their teachers are paid promptly to reduce distraction and financial stress to be able to focus on implementation policy directives.